Beach volleyball set and technical performance indicators for elite women`s teams - Giatsis, G.; Lola, A.; Drikos, S.; López-Martínez, A. B.; Perez-Turpin, J. A. (Journal of Human Sport & Exercise, 2023)
This study aimed to investigate the beach volleyball set and technical performance indicators that best discriminate between winning and losing elite women`s teams in set according to the final score differences of the set. The data have been collected from all sets played (N = 236) in the women`s beach volleyball 2022 World Championship. Cluster analysis established two types of 21 points sets (S-21): balanced (S-21B) with a difference from 2-5 points and unbalanced (S-21U) with a difference >5 points. A discriminant function analysis indicated which skill(s) significantly contribute to winning in each type of set. The results of this study revealed that the teams that won S-21B, S-21U and S-15 had better performance than their opponents in set indicators (attack, block, serve, opponent errors) and technical indicators (attack kill percent, attack efficiency, and serve efficiency). Attack points and attack kill percent were the most important predictors of a team's success in terms of set and technical indicators, respectively. In summary, the attack kill percent is the most important indicator in elite women`s beach volleyball in every type of set. However, serve aces per set point significantly increases the probability of winning a set in every type of 21-point set, while block per set points contributes equally significantly in 15-point sets. Despite the high level of blocking, women's teams must avoid attack errors to improve their chances of winning a set. The study`s findings highlight the importance of the offensive ability to win a set, in women`s elite beach volleyball.